Analisis Temperatur Terhadap Perpindahan Panas pada Sistem Pendingin - Lazahimu, Erlina; Safiuddin, La Ode; Hasanudin, La (Jurusan Pendidikan Fisika, 2020)
This study aims to: (1) determine the heat transfer process of the room area; (2) to determine the effect of sensible heat load on the performance of air conditioner / AC. This study used an experimental method to obtain data on the temperature of the external coolant load, the load on the inner cooler, the area of the room and the surface area data for each cooling load. The results of this study indicate that: the heat load greatly affects the performance of the air conditioner (AC) in producing a comfortable temperature in the room, such as in the meeting room of the BNN Province of SULTRA using 2 PK AC capacity with a total cooling load of 34,979 Btu / hr or 8,744.75 kcal, so that you have to add an AC unit with a minimum capacity of 2 PK to obtain the calorific value that can be moved by the AC (Q1) is greater than the heat load generated by the room (Q2), which is 36,000 Btu / hr> 34,979 Btu / hr or 9,000 kcal> 8,744.75 kcal so that comfortable conditions will be obtained.